2015
DOI: 10.1371/journal.pone.0129622
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Total Sedentary Time and Screen Time in 9–11 Year-Old Children around the World: The International Study of Childhood Obesity, Lifestyle and the Environment

Abstract: PurposePreviously, studies examining correlates of sedentary behavior have been limited by small sample size, restricted geographic area, and little socio-cultural variability. Further, few studies have examined correlates of total sedentary time (SED) and screen time (ST) in the same population. This study aimed to investigate correlates of SED and ST in children around the world.MethodsThe sample included 5,844 children (45.6% boys, mean age = 10.4 years) from study sites in Australia, Brazil, Canada, China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
201
8
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(251 citation statements)
references
References 37 publications
(55 reference statements)
10
201
8
16
Order By: Relevance
“…Second, despite the large internationally diverse sample included, none of the countries had a nationally representative sample; hence the results may not be generalizable to country sites. 44 Third, AST was defined based only on the 'main' mode of transport for the journey 'to school'. Thus we assumed that both journeys were the same.…”
Section: Discussionmentioning
confidence: 99%
“…Second, despite the large internationally diverse sample included, none of the countries had a nationally representative sample; hence the results may not be generalizable to country sites. 44 Third, AST was defined based only on the 'main' mode of transport for the journey 'to school'. Thus we assumed that both journeys were the same.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have 66 consistently found that physical activity is associated with obesity indicators independent of sedentary 67 time (Ekelund et al, 2014;Katzmarzyk et al, 2015). However, the association between objective 68 sedentary time and obesity markers independent of physical activity is less clear (Cliff et al, 2016; 69 Ekelund et al, 2014).…”
mentioning
confidence: 99%
“…There has been an increased interest in research related to sedentary behavior (SB) and its correlates around the world 1,2 . SB, typically defined as activities that do not increase energy expenditure substantially above the resting level (≤1.5 METs) while in a sitting or reclining posture such as sleeping, sitting, lying down, and watching television, and other forms of screenbased entertainment 3 , has been measured by accelerometry as an objective approach and self -or proxy-report questionnaires, as a subjective approach 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, approximately 60% of Portuguese children aged11-year-old watched TV for ≥2h on weekdays 12 , while 12.2% of children aged between 6-13 year-oldspent less than 1.5 hours watching TV and playing video games, either on weekdays or weekends 13 . Thus, we target to contribute in this field of knowledge, pointing out differences between distant countries geographically and culturally that should be considered whereas worldwide studies are recently paying attention on the increased prevalence of ST among children and adolescents [14][15][16] and it has been reported with negative health outcomes 1,[17][18][19] . Therefore, this study aimed to verify differences in ST (i.e.…”
mentioning
confidence: 99%